Pengaruh Kehidupan Rohani Guru Pendidikan Agama Kristen Dan Implikasinya Terhadap Pertumbuhan Iman Peserta Didik Di SDN Semplak 2 Kota Bogor - Yanuar, Yanuar; Mujiono, John Gershom (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
Christian religious education in school environments plays a central role in shaping the character and spiritual growth of students. However, Christian religious education teachers at SDN Semplak 2 Kota Bogor face various challenges, ranging from personal factors to complex social dynamics, which can affect their effectiveness in guiding the spiritual growth of students. In this study, the author will identify several aspects related to Christian religious education in schools due to the existing knowledge gap regarding the impact of teachers' spiritual lives on the spiritual growth of students at SDN Semplak 2 Kota Bogor. Therefore, this study aims to fill this gap by analyzing the influence of teachers' spiritual lives on the spiritual growth of students. It is hoped that this research will provide valuable insights for the development of more effective Christian religious education curricula and help improve the competence of teachers in guiding the spiritual growth of students in the school environment. The research method used is interviews and observations as data collection tools. The research respondents consist of Christian religious education teachers and students at SDN Semplak 2. The results of the data analysis indicate a significant influence between the spiritual lives of teachers and the spiritual growth of students. The implications of these findings emphasize the importance of the role of Christian religious education teachers in shaping the character and faith of students in the school environment. This study can provide important input for curriculum development and the mentoring of Christian religious education teachers at SDN Semplak 2 in improving the quality of Christian religious education and the spiritual growth of students.